0245 Relationship of Chronotype with Sleep Duration, Daytime Sleepiness, and Sustained Attention in High School Students: A Pilot Study. (27th May 2020) - Morrison, S W; Scheer, F A; Mason, I C
Abstract: Introduction: People with a later chronotype typically sleep later and perform better later in the day. In an early high school schedule, students with later chronotypes earn lower average grades than those with earlier chronotypes. However, other effects of late chronotype on high school students are poorly understood. This study examined the relationship of chronotype with sleep duration, daytime sleepiness and sustained attention in high school students. Methods: This study was conducted at Byram Hills High School in Armonk, NY, where classes begin at 7:45am. During three class periods, 36 participants (female n=24, n=12, 14–17 years old) completed the Morning-Eveningness Questionnaire (MEQ), Karolinska Sleepiness Scale (KSS), and Psychomotor Vigilance Test (PVT) during their class. Subjects recorded time spent on homework/extracurricular activities and bedtime/waketime from the night prior to the assessment. Results: Later chronotype (lower MEQ score) was significantly associated with later bedtime, shorter sleep duration, and increased sleepiness (r=-0.82, p<0.001; r=0.72, p<0.001; and r=-0.40, p=0.016; respectively). Shorter sleep duration was significantly correlated with increased sleepiness (r=-0.34, p=0.045). Increased workload (time on homework/extracurriculars) was significantly associated with later bedtime (r=0.42, p=0.011). Chronotype, sleep duration, and sleepiness showed no significant association with PVT scores (r=-0.16, p=0.360; r=-0.10, p=0.933; r=0.09, p=0.619, respectively); however, increased workload was significantly associated with increased PVT scores (r=-0.35, p=0.041). Conclusion: These results are important for the wellbeing of high school students, as they show relationships between late chronotype, short sleep, and increased sleepiness during class in an early school schedule. Further research is needed to determine the best school schedule for high school students based on individual differences in chronotype. Support: We thank the Authentic Science Research program at Byram Hills High School, specifically teachers Mrs. Stephanie Greenwald, Dr. Caroline Matthew, and Mrs. Megan Salomone.